2009
DOI: 10.1016/j.biomaterials.2009.05.033
|View full text |Cite
|
Sign up to set email alerts
|

The use of three-dimensional nanostructures to instruct cells to produce extracellular matrix for regenerative medicine strategies

Abstract: Synthetic polymers or naturally-derived extracellular matrix (ECM) proteins have been used to create tissue engineering scaffolds; however, the need for surface modification in order to achieve polymer biocompatibility and the lack of biomechanical strength of constructs built using proteins alone remain major limitations. To overcome these obstacles, we developed novel hybrid constructs composed of both strong biosynthetic materials and natural human ECM proteins. Taking advantage of the ability of cells to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…The methodology is sensitive to changes that occur in rsif.royalsocietypublishing.org J R Soc Interface 10: 20130263 diseases such as sclerodermia or in skin or other epithelial cancer types [139 -141]. Other application examples are the investigation of heart valves and cardiac [63] or corneal tissue [142,143]. To image collagen I with SHG, excitation wavelengths from 720 to 960 nm [62] can be used, and for detection, a bandpass filter with centre wavelength at half the excitation wavelength is applied (e.g.…”
Section: Imaging Cellular Proteinsmentioning
confidence: 99%
“…The methodology is sensitive to changes that occur in rsif.royalsocietypublishing.org J R Soc Interface 10: 20130263 diseases such as sclerodermia or in skin or other epithelial cancer types [139 -141]. Other application examples are the investigation of heart valves and cardiac [63] or corneal tissue [142,143]. To image collagen I with SHG, excitation wavelengths from 720 to 960 nm [62] can be used, and for detection, a bandpass filter with centre wavelength at half the excitation wavelength is applied (e.g.…”
Section: Imaging Cellular Proteinsmentioning
confidence: 99%
“…Alignment has also been observed along the direction of grooves formed in laminin [18]. We have also shown that incorporating nanostructures into a culture can influence cellular behavior [19]. Additionally, cellular morphology is greatly different between in vitro 2D culture and in vivo 3D native tissue, and the addition of this 3D component has become more widespread in many research groups.…”
Section: Discussionmentioning
confidence: 73%
“…Because ECM is a fibrillar meshwork including the growth factors (cytokines, vascular endothelial growth factor), structural proteins (collagen and elastin), adhesion proteins (fibronectin and laminin), and glycosaminoglycans (chondroitin sulfate), these components arrange in a biochemically complex and intricately three-dimensional structure, which constitutes a barrier for diffusion and convection, and provides tissues with mechanical strength and elastic properties. Katja developed novel hybrid constructs composed of poly and natural ECM, and these constructs exhibited excellent biomechanical property and allowed attachment and migration of adipose tissue-derived stem cells [16]. ECM component, mainly consist of type IV collagen, Fibronectin, laminin, and growth factors, had been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%